Short-Term High-Intensity Interval Exercise Promotes Motor Cortex Plasticity and Executive Function in Sedentary Females - Hu, Min; Zeng, Ningning; Gu, Zhongke; Zheng, Yuqing; Xu, Kai; Xue, Lian; Leng, Lu; Lu, Xi; Shen, Ying; Huang, Junhao (Frontiers in Human Neuroscience, 2021)
Previous research has demonstrated that regular exercise modulates motor cortical plasticity and cognitive function, but the influence of short-term high-intensity interval training (HIIT) remains unclear. In the present study, the effect of short-term HIIT on neuroplasticity and executive function was assessed in 32 sedentary females. Half of the participants undertook 2 weeks of HIIT. Paired-pauses transcranial magnetic stimulation (ppTMS) was used to measure motor cortical plasticity via short intracortical inhibition (SICI) and intracortical facilitation (ICF). We further adapted the Stroop task using functional near-infrared spectroscopy (fNIRS) to evaluate executive function in the participants. The results indicated that, compared with the control group, the HIIT group exhibited decreased ICF. In the Stroop task, the HIIT group displayed greater activation in the left dorsolateral prefrontal cortex (DLPFC) and left orbitofrontal cortex (OFC) even though no significant difference in task performance was observed. These findings indicate that short-term HIIT may modulate motor cortical plasticity and executive function at the neural level.